ALMA photometry of extragalactic radio sources. Issue 1 (15th February 2019) - Bonato, M; Liuzzo, E; Herranz, D; González-Nuevo, J; Bonavera, L; Tucci, M; Massardi, M; De Zotti, G; Negrello, M; Zwaan, M A
Abstract: We present a new catalogue of ALMA (Atacama Large Millimeter/submillimeter Array) observations of 3364 bright, compact radio sources, mostly blazars, used as calibrators. These sources were observed between 2011 May and 2018 July, for a total of 47 115 pointings in different bands and epochs. We have exploited the ALMA data to validate the photometry given in the new Planck multifrequency Catalogue of Non-Thermal sources (PCNT), for which an external validation was not possible so far. We have also assessed the positional accuracy of Planck catalogues and the PCNT completeness limits, finding them to be consistent with those of the Second Planck Catalogue of Compact Sources. The ALMA continuum spectra have allowed us to extrapolate the observed radio source counts at 100 GHz to the effective frequencies of ALMA bands 4, 6, 7, 8, and 9 (145, 233, 285, 467, and 673 GHz, respectively), where direct measurements are scanty, especially at the three highest frequencies. The results agree with the predictions of the Tucci et al. model C2Ex, while the model C2Co is disfavoured.